Role of prophylactic oophorectomy at the time of hysterectomy in ovarian cancer prevention in Thailand - Charoenkwan K. (2014)
Aim: To determine the impact of prophylactic oophorectomy on ovarian cancer prevention in Thai women by estimating the magnitude of reduction in ovarian cancer incidence in Thailand if the procedure was routinely offered. Methods: A database of 752 women with epithelial ovarian cancer treated at Chiang Mai University Hospital between January 1990 and December 2001 was reviewed in an attempt to identify those who had hysterectomy performed for indications other than ovarian and corpus cancer with conservation of one or both ovaries prior to diagnosis of ovarian cancer. Pertinent clinical and pathologic data of the women in this subset were further reviewed in detail. Results: Of 752 ovarian cancer patients, 13 (1.73%) had hysterectomy performed prior to the diagnosis of ovarian cancer with only one woman (0.13%) having had a hysterectomy at the age of 45 or above. The mean interval between the hysterectomy and the diagnosis of ovarian cancer was 9.9 years (range 2-25 years). Considering the rate of prior hysterectomy at age 45 or beyond of 0.13% and the annual national ovarian cancer incidence of 1252 cases, an estimated one to two cases of ovarian cancer could be prevented annually if prophylactic bilateral oophorectomy at the time of hysterectomy in a woman age 45 or beyond were routinely offered in Thailand. Conclusion: Prophylactic oophorectomy at the time of hysterectomy in general Thai population as a preventive measure for subsequent ovarian cancer should not be recommended without complete knowledge of patients' socioeconomic background and propensity to comply with hormone replacement therapy regimens.